Modification of Brassica seed oil by antisense expression of a stearoyl-acyl carrier protein desaturase gene. - Knutzon, D S (1992)
Molecular gene transfer techniques have been used to engineer the fatty acid composition of Brassica rapa and Brassica napus (canola) oil. Stearoyl-acyl carrier protein (stearoyl-ACP) desaturase (EC 1.14.99.6) catalyzes the first desaturation step in seed oil biosynthesis, converting stearoyl-ACP to oleoyl-ACP. Seed-specific antisense gene constructs of B. rapa stearoyl-ACP desaturase were used to reduce the protein concentration and enzyme activity of stearoyl-ACP desaturase in developing rapeseed embryos during storage lipid biosynthesis. The resulting transgenic plants showed dramatically increased stearate levels in the seeds. A continuous distribution of stearate levels from 2% to 40% was observed in seeds of a transgenic B. napus plant, illustrating the potential to engineer specialized seed oil compositions.